2021
DOI: 10.1111/jcmm.16586
|View full text |Cite
|
Sign up to set email alerts
|

Construction of circRNA‐miRNA‐mRNA network in the pathogenesis of recurrent implantation failure using integrated bioinformatics study

Abstract: This research attempted to elucidate the molecular components are involved in the pathogenesis of recurrent implantation failure (RIF). We initially identified that 386 mRNAs, 144 miRNAs and 2548 circRNAs were differentially expressed (DE) in RIF and then investigated the genetic cause of the observed abnormal expression by constructing a circRNA‐miRNA‐mRNA network considering the competing endogenous RNA theory. We further analysed the upstream transcription factors and related kinases of DEmRNAs (DEMs) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…MiR-181d has the responsibility to regulate the acute stress response in thymocytes via targeting LIF (Sun et al, 2014). Combing mRNA microarray GSE111974 with miRNA microarray GSE71332, Ahmadi and colleagues constructed a circRNA-miRNA-mRNA network in RIF, and found that miR-29c might be a crucial miRNA, which is consistent with our analysis (Ahmadi et al, 2022). In addition, overexpression of miR-29 has been reported to impair endometrial receptivity by inhibiting the differentiation of endometrial stromal cells and regulating decidualization (Zhou et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…MiR-181d has the responsibility to regulate the acute stress response in thymocytes via targeting LIF (Sun et al, 2014). Combing mRNA microarray GSE111974 with miRNA microarray GSE71332, Ahmadi and colleagues constructed a circRNA-miRNA-mRNA network in RIF, and found that miR-29c might be a crucial miRNA, which is consistent with our analysis (Ahmadi et al, 2022). In addition, overexpression of miR-29 has been reported to impair endometrial receptivity by inhibiting the differentiation of endometrial stromal cells and regulating decidualization (Zhou et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…GO analysis demonstrated that DEGs in RIF were primarily enriched in lipid metabolism and immune processes. In KEGG analysis, the NF-κB, TNF, and adipocytokine signaling pathways were linked together, which is consistet with similar RIF studies showing dysregulated NF-κB and TNF pathways [ 24 , 38 , 39 , 40 ]. GSEA results demonstrated that RIF was significantly enriched in downregulated graft-versus-host disease, allograft rejection, complement and coagulation cascades, antigen processing and presentation, upregulated fatty acid biosynthesis, ovarian steroidogenesis, and steroid hormone biosynthesis.…”
Section: Discussionmentioning
confidence: 60%
“…The results of our study indicate that upregulated lipid metabolism pathways and correlations between dysregulated immune and metabolic pathways also exist in RIF. The study by Ahmadi et al [ 39 ] showed that steroid hormone biosynthesis was a potentially disrupted pathway in RIF patients. According to the Spearman correlation coefficient, fatty acid biosynthesis was significantly negatively correlated with immune pathways and significantly positively correlated with ovarian steroidogenesis and steroid hormone biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…An integrated bioinformatics analysis revealed that 386 mRNAs, 144 miRNAs, and 2548 circRNAs were differentially expressed in patients with RIF compared to fertile women [142] . Furthermore, based on the ceRNA network of circRNA–miRNA–mRNA interactions in RIF, the researchers found that arrhythmogenic right ventricular cardiomyopathy (ARVC), hypertrophic cardiomyopathy (HCM), the TNF signaling pathway, and steroid hormone biosynthesis may be disrupted in patients with RIF due to aberrant miRNA expression patterns [142] . Owing to the differential expression of miRNAs, a novel diagnostic platform named PanelChip was designed to evaluate endometrial miRNA profiles in patients with non-RIF/RIF.…”
Section: Mirnas In Abnormal Endometrium Functions and Pathologiesmentioning
confidence: 99%
“…Most of the identified miR-NAs were enriched in the immune response, inflammation process, metabolic process, and cell cycle pathway, which are also involved in endometrial receptivity, decidualization, and subsequent embryo implantation events in the endometrium. An integrated bioinformatics analysis revealed that 386 mRNAs, 144 miRNAs, and 2548 circRNAs were differentially expressed in patients with RIF compared to fertile women [142] . Furthermore, based on the ceRNA network of circRNA-miRNA-mRNA interactions in RIF, the researchers found that arrhythmogenic right ventricular cardiomyopathy (ARVC), hypertrophic cardiomyopathy (HCM), the TNF signaling pathway, and steroid hormone biosynthesis may be disrupted in patients with RIF due to aberrant miRNA expression patterns [142] .…”
Section: Mirna In Repeated Implantation Failure and Recurrent Miscarr...mentioning
confidence: 99%